Great white sharks ebook - London, Martha (Wild About Animals., 2020)
This series introduces readers to some of the most exceptional creatures of the animal kingdom. Includes fun facts and what makes them unique and interesting from other animals. Features informative sidebars, detailed infographics, vivid photos, and a glossary.